2014
DOI: 10.1016/j.resp.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reflux laryngitis on non-nutritive swallowing in newborn lambs

Abstract: Reflux laryngitis in infants may be involved not only in laryngeal disorders, but also in disorders of cardiorespiratory control through its impact on laryngeal function. Our objective was to study the effect of reflux laryngitis on non-nutritive swallowing (NNS) and NNS-breathing coordination. Two groups of six newborn lambs, randomized into laryngitis and control groups, were surgically instrumented for recording states of alertness, swallowing and cardiorespiratory variables without sedation. A mild to mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…We have previously shown that NNS beginning in inspiration are predominant over NNS beginning in expiration in lambs (Reix et al, 2003). In addition, we have reported that NNS-breathing coordination in lambs is unaltered by various neonatal conditions such as nasal application of continuous or intermittent positive airway pressure (Samson et al, 2005), hypoxia (Duvareille et al, 2007), preterm birth (Reix et al, 2004) and reflux laryngitis (Brisebois et al, 2010), suggesting that NNSbreathing coordination is established well before birth, in keeping with its importance for preventing both lung aspiration and respiratory inhibition. Until now, hypercapnia in newborn lambs (Duvareille et al, 2007) and volition in adult humans (Kelly et al, 2007) were the only conditions known to alter NNS-breathing coordination.…”
Section: Non-nutritive Swallowing-breathing Coordinationmentioning
confidence: 79%
“…We have previously shown that NNS beginning in inspiration are predominant over NNS beginning in expiration in lambs (Reix et al, 2003). In addition, we have reported that NNS-breathing coordination in lambs is unaltered by various neonatal conditions such as nasal application of continuous or intermittent positive airway pressure (Samson et al, 2005), hypoxia (Duvareille et al, 2007), preterm birth (Reix et al, 2004) and reflux laryngitis (Brisebois et al, 2010), suggesting that NNSbreathing coordination is established well before birth, in keeping with its importance for preventing both lung aspiration and respiratory inhibition. Until now, hypercapnia in newborn lambs (Duvareille et al, 2007) and volition in adult humans (Kelly et al, 2007) were the only conditions known to alter NNS-breathing coordination.…”
Section: Non-nutritive Swallowing-breathing Coordinationmentioning
confidence: 79%